2017
DOI: 10.1098/rspb.2017.1830
|View full text |Cite
|
Sign up to set email alerts
|

Men's preferences for women's body odours are not associated with human leucocyte antigen

Abstract: Body odours reportedly portray information about an individual's genotype at the major histocompatibility complex (MHC, called human leucocyte antigen, HLA, in humans). While there is strong experimental support for MHC-associated mating behaviour in animals, the situation in humans is more complex. A lot of effort has been spent on testing HLA-associated odour preferences of women. To date, only very few studies have looked at HLA-linked olfactory preferences in men and these studies have revealed inconsisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…The pads were thawed three hours before the respective rating session started and were placed in separate 500 ml opaque glass jars (cf. [1,41,42]). Three research assistants smelled the pads and confirmed that none was contaminated with extraneous odours (e.g.…”
Section: (D) Odour Rating Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The pads were thawed three hours before the respective rating session started and were placed in separate 500 ml opaque glass jars (cf. [1,41,42]). Three research assistants smelled the pads and confirmed that none was contaminated with extraneous odours (e.g.…”
Section: (D) Odour Rating Proceduresmentioning
confidence: 99%
“…To assess the odour preferences we closely followed the procedures reported in [1,41]. To prepare for the rating session, odour raters (all male) were asked not to eat and to refrain from drinking caffeinated or alcoholic beverages for one hour before testing, as these activities are known to affect smelling ability.…”
Section: (D) Odour Rating Proceduresmentioning
confidence: 99%
“…In our recent study published in Proceedings of the Royal Society B [1], we investigated the effects of major histocompatibility complex (MHC; or human leucocyte antigen system, HLA in humans) on men's preferences for women's body odours. Using rigorous methods, we found no evidence that men find body odours of HLA-dissimilar women more attractive than odours of HLAsimilar women.…”
mentioning
confidence: 99%
“…So, it is conceivable that men rely less on HLA-mediated odour cues when choosing their mates than women. We note that apart from our study [1], only four studies have included men as odour raters. Two of these studies report no preference HLA-dissimilar women [13,14], and two suggest that men show a preference for body odours of HLAdissimilar women [6,15] (note that Wedekind & Furi included odours of only two women).…”
mentioning
confidence: 99%
See 1 more Smart Citation